2014
DOI: 10.1007/s11064-014-1422-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebrospinal Fluid Concentrations of TGFβ1 in Patients with Drug-Resistant Epilepsy

Abstract: Transforming growth factor beta (TGFβ) signaling participates in pathogenesis of epilepsy. TGFβ1, as a transmitter of TGFβ signaling, might be a useful marker for predicting the prognosis of patients with epilepsy. The present study aimed to measure TGFβ1 level in the cerebrospinal fluid (CSF) of patients with drug-resistant epilepsy and non-resistant epilepsy. A total of 43 patients with epilepsy were recruited, 28 were non-resistant epilepsy subgroup, 15 drug-resistant epilepsy subgroup. 11 patients with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…TGF-β signaling is activated and components of the pathway are upregulated in human and experimental epilepsy. TGF-β1 levels are increased in the CSF of patients with drug-resistant epilepsy [300]. TGFBR1 expression is significantly upregulated in temporal neocortices of patients with TLE [301].…”
Section: Epilepsymentioning
confidence: 99%
“…TGF-β signaling is activated and components of the pathway are upregulated in human and experimental epilepsy. TGF-β1 levels are increased in the CSF of patients with drug-resistant epilepsy [300]. TGFBR1 expression is significantly upregulated in temporal neocortices of patients with TLE [301].…”
Section: Epilepsymentioning
confidence: 99%
“…In addition, TRPV1 inhibits the microglial M2 phenotype, which is also a complementary pathway in epileptogenesis. Some studies have already confirmed that M2 markers are upregulated or downregulated during epileptogenesis (Xanthos and Sandkuhler, 2014; Yu et al, 2014; Benson et al, 2015; Ali et al, 2017), and insufficient Arg1 or Ym1 is a susceptibility element for epileptogenesis (Boche et al, 2013; Benson et al, 2015; Cantero et al, 2016). One recent study reported that microglial-specific expression levels of M2 markers (Arg1, Ym1) were significantly downregulated at the early chronic phase in a pilocarpine-induced epilepsy model (Benson et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Recent mounting evidences show that TGF-β signaling pathways are intricated in epileptogenesis ( 92 ). In resected brain regions from epileptic patients and animal models, the increased expression of TβR1 is observed in cortex, amygdala, and hippocampus, particularly in the piriform cortex ( 61 , 93 ). Activation of TGF-β signaling pathways in astrocytes can mediate albumin uptake, potassium (K + ) buffering, glutamate metabolism, pro-inflammatory mediators releasing, and synaptogenesis, which collectively lead to neuronal hyperexcitability and epileptogenesis ( 94 , 95 ).…”
Section: Pro-inflammatory Molecules In Epilepsymentioning
confidence: 99%